2016
DOI: 10.3390/ijms17081243
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser Patterning of the Biopolymer Chitosan for Biofilm Formation

Abstract: Controlling microbial growth is crucial for many biomedical, pharmaceutical and food industry applications. In this paper, we used a femtosecond laser to microstructure the surface of chitosan, a biocompatible polymer that has been explored for applications ranging from antimicrobial action to drug delivery. The influence of energy density on the features produced on chitosan was investigated by optical and atomic force microscopies. An increase in the hydrophilic character of the chitosan surface was attained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Moreover, SEM can be employed to study the effect of substrate stiffness or biofunctionalization on proliferation and differentiation of Scanning electron microscopy is a technique that uses a focused beam of electrons to scan a desired sample while detecting the emitted secondary electrons. Characteristics of various types of materials can be identified, including but not limited to surface relief microstructures developed on chitin-derived biopolymers [114], the surface morphology of porous biopolymer nanofibers [107], rough nanostructures [110], as well as many other (biodegradable) structures [20,21,52,111,[115][116][117][118][119][120][121]. With SEM, specimens are observed in a vacuum, therefore the studied biological samples are required to be dry and fixed on a hard substrate.…”
Section: Microscopic Techniques For Cell Proliferation and Differenti...mentioning
confidence: 99%
“…Moreover, SEM can be employed to study the effect of substrate stiffness or biofunctionalization on proliferation and differentiation of Scanning electron microscopy is a technique that uses a focused beam of electrons to scan a desired sample while detecting the emitted secondary electrons. Characteristics of various types of materials can be identified, including but not limited to surface relief microstructures developed on chitin-derived biopolymers [114], the surface morphology of porous biopolymer nanofibers [107], rough nanostructures [110], as well as many other (biodegradable) structures [20,21,52,111,[115][116][117][118][119][120][121]. With SEM, specimens are observed in a vacuum, therefore the studied biological samples are required to be dry and fixed on a hard substrate.…”
Section: Microscopic Techniques For Cell Proliferation and Differenti...mentioning
confidence: 99%
“…The group of Alves et al for example showed experimentally that Fs laser created grooves, separated by distance of 8–12 µm and with channel width in the range 0.54 µm to 1.33 µm favor S. aureus adhesion. A further increase in surface roughness did not favor the bacteria adhesion and biofilm formation [ 51 ]. It is reported by other research groups that an intact bacteria biofilm occurred much faster when the surface roughness was greater than 0.8 μm as the contact area between the bacteria cell and the surface is increased [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the rapid prototyping is still restricted by the long production time which leads to high costs. Laser-assisted microfabrication techniques have been thoroughly investigated in the literature as a promising alternative for microsystems [22] and microfluidic systems [19][20][21][22]. Furthermore, ultrafast laser beams have been successfully employed in the fabrication of thin film optoelectronics and sensors [28,29].…”
Section: Introductionmentioning
confidence: 99%